A Rebel without a Cause and His PTSD: Depictions of Mental Illness in The Winchesters - Anna Caterino (Series. International journal of tv serial narratives)
The Winchesters (The CW, 2022) tells the story of John Winchester (Drake Rodger) after his return from Vietnam. The show seeks to explore his PTSD through the monster of the week format, exploiting the conventions of the horror genre without adhering to outdated and negative stereotypes. In doing so, showrunner Robbie Thompson challenges Supernatural’s (The CW, 2005-2020) narrative and the one proposed by other media focused on the same issues. However, the references made to Western ideals of masculinity ensure an all but ‘sanitized’ depiction that ultimately asks the audience to question the limits of empathy and their own prejudices. This essay aims to analyze the show through the lens of medical humanities, focusing on the depiction of John as a patient-person and how his PTSD is depicted throughout the show.